Evaluation of Teacher Readiness in Geography Lesson Planning at State Senior High Schools in Yogyakarta City for the Implementation of the Merdeka Curriculum - Fathoni, M. Rizal; Nursa'ban, Muhammad (Universitas Negeri Yogyakarta, 2025)
The structural changes in the Merdeka Curriculum, particularly in the Geography subject, have made it challenging for teachers to adopt and adapt. This study evaluates teachers' readiness in Geography lesson planning, analyzes obstacles, and provides recommendations for implementing the Merdeka Curriculum using Stufflebeam's Context, Input, Process, Product (CIPP) evaluation model. The research focuses on teachers' readiness to implement the Merdeka Curriculum, with geography teachers from six high schools (SMA) in Yogyakarta City categorized as independently changing schools, as the research subjects. The evaluation results indicate that Geography teachers in Yogyakarta City high schools are highly prepared for lesson planning, with an overall score of 66, based on Context: 86.5, Input: 36.8, Process: 91, and Product: 43. Key indicators include understanding the curriculum, facilities, lesson planning, assessment processes, and teaching modules. However, teachers still face challenges due to curriculum restructuring, requiring them to understand fundamental concepts. Training and in-depth material studies are essential to enhance teachers' soft skills and optimize curriculum implementation.